The influence of audit committees’ characteristics on earnings quality: evidence from Indonesia - NELLIYANA NELLIYANA (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2015)
The objective of this research is to get empirical evidence audit committees’ characteristics: financial expertise, number of meetings, audit committees’ sizes that moderate the effects of unexpected earnings to cumulative abnormal return. This research also includes independent variables that theoretically influence the relation of unexpected earnings to cumulative abnormal return such as CEO stock ownerships, earnings persistence, market beta, percentage of reporting loss and discretionary accruals. The sample of this research is companies listed in Indonesia Stock Exchange (IDX) during year 2007 to 2009. This research uses 147 data with 49 companies selected per year. The analysis tools used in this research is multiple linear regression. The result shows that financial expertise, number of meetings, audit committees’ sizes and others variables altogether do not moderate the effects of unexpected earnings to cumulative abnormal return or earnings quality reported in financial report. It shows that investors in Indonesia do not consider the characteristics of audit committees in their investment decision making process and the characteristic of audit committees itself does not influence the quality of reported earnings.